Being a State and States of Being in Highland Georgia - Klavs Sedlenieks (Journal of Ethnology and Folkloristics)
This review of the book of Florian Mühlfried Being a State and States of Being in Highland Georgia summarizes the central argument wrapped around new insights into what means to be a citizen of an erratic state and what cultural mechanisms have been developed by the inhabitants of the Highland Georgian region of Tusheti to cope with the unpredictability of the state policies. The cultural mechanisms allow for simultaneous being involved in and keeping distance from the state. The review gives also some critical points.